Complex regional pain syndrome (CRPS) in orthopaedics: an overview. Issue 4 (August 2019) - Cowell, Fiona; Gillespie, Sharon; Narayan, Badri; Goebel, Andreas
Abstract: Complex regional pain syndrome (CRPS) is a debilitating and painful condition in a limb, occurring most often after trauma and surgery, and associated with nerve, skin and bone abnormalities. The condition is poorly understood, often diagnosed late and national recommendations are not yet generally integrated into standard practice. Whilst signs and symptoms generally improve within 6 months of onset, many patients have long-term pain and disability, and the costs of managing chronic pain and disability are substantial. This paper provides an overview of the latest understanding of CRPS and national guidelines, explains how to make a diagnosis, describes initial treatment and controversies in orthopaedic care and explores the implications of CRPS to the orthopaedic team.